The best interest of the children, once more about the need to create an autonomous concept of their habitual residence. Order of October 24, 2019 Twelfth Section of the Provincial Audience of Barcelona - Pérez Martín, Lucas Andrés (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
Once more we appreciate the negative effects due to the lack of will of the European and National Legislator to specify an autonomous concept of habitual residence for boys and girls, which allows the definition of fact criteria to define it. This causes that a procedure of preliminary provisional measures, hich are necessarily urgent, takes nineteens months to start. Such delay clearly damages the interest of boys and girls to access to an effective judicial protection without undue delay. The ruling of October 24, 2019 of the twelfth section of the Provincial Court of Barcelona resolves an initial erroneous assessment from the Court of First Instance number 15 of Barcelona, which includes that the habitual residence of a minor would be absolutely avoidable, if the judge had clear legal criteria to determine it. The jurisprudential doctrine exists, but even so, after the amendment of Brussels II bis, those of us who advocate the regulation concretion of the concept will continue to await the necessary reaction from the European Legislator.
Keywords: Parental responsibility; habitual residence of children; Autonomous concept; best in¬terests of the child